Attitudes toward fertility and childbearing among female University students (Universa Medicina, 2023)
BACKGROUNDIn recent years, there has been a significant decrease in childbearing rates in many parts of the world. Young people who delay their marriage plans for various reasons also indirectly delay their childbearing to advanced ages. Postponed childbearing may lead to increased health risks for both mother and child. This study aimed to determine attitude towards fertility and childbearing in female university students.METHODSThis cross-sectional study involved 259 female university students. The data were collected with Attitudes Toward Fertility and childbearing Scale (AFCS). Data were analyzed using t test and one-way ANOVA.RESULTSIn the study 92.7% of the students wanted to become a future mother. The importance of fertility for the future mean score of the students with low income level (21.56±8.14) was found to be lower than the students with medium (25.80±6.51) and high income level (25.29±4.37) (p